Community-Based Conflict Resolution in Iron Sand Mining at Pasar Seluma Village - Henny Aprianty; Heru Purnawan; Hariangga Hariangga; Deni Triyanto; Kismartini Kismartini (Jurnal Administrasi Publik (Public Administration Journal), 2026)
This study examines community-based conflict resolution in iron sand mining management in Pasar Seluma Village, Indonesia. It addresses persistent conflicts involving local communities, mining companies, and government authorities by identifying their root causes and proposing a policy-oriented resolution model. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and document analysis. The analysis integrates Ralf Dahrendorf’s social conflict theory and Johan Galtung’s peaceful conflict resolution framework, with data credibility ensured through source triangulation. The findings reveal that conflicts stem from prolonged community resistance since 2010, inadequate corporate communication, incomplete licensing procedures, environmental degradation concerns, and unresolved social grievances. These conditions generate both manifest and latent conflicts that undermine governance legitimacy. The study’s novelty lies in formulating a Grassroots Conflict Resolution Model, which reframes community participation not merely as consultation but as a core governance mechanism in resource management. Unlike top-down regulatory approaches, this model emphasizes early-stage engagement, local power redistribution, and justice-oriented mediation. From a policy perspective, the study provides actionable insights for local governments to design inclusive, participatory, and conflict-sensitive mining governance frameworks. The model contributes both theoretically and practically to public policy discourse on managing natural resource conflicts in marginalized and resource-rich regions.